The Filipino Woman and/in the Filipino Rebel - Sicat, Maria Teresa Martinez (Review of Women's Studies; Vol 6 No 1 (1996): Review of Women's Studies Volume V, Number 2 - Volume VI, Number 1 (1996))
---